Sosialisasi Infrastruktur Sanitasi Permukiman Berbasis Kesehatan Lingkungan Desa Raba Kabupaten Bima: Socialization Of Environmental Health-Based Settlement Sanitation Infrastructure Raba Village Bima District - ERDIANSYAHPUTRA, B; Sharwanda Asfarina; Syahrir (Journal of Excellence Humanities and Religiosity, 2025)
Adequate sanitation infrastructure is a critical component to ensure the environmental sustainability and public health of settlements. This infrastructure must be properly designed, constructed, and maintained to ensure health and the environment. This service aims to provide information about environmentally friendly sanitation techniques to the community. In order to get a data base planning as an effort to manage sustainable sanitation. The method used is by conducting socialisation related to sanitation infrastructure, counselling on clean and healthy lifestyles and verifying the feasibility of settlement sanitation. The results of the socialisation activities showed that the need for sanitation infrastructure in Raba Village is still very much, this is because no one has access to sanitation or wastewater treatment systems that meet technical standards and based on MBR there are still 17, 14 and 11 units that do not have access to sanitation in each hamlet in Raba Village, Wawo Sub-district, Bima Regency.